Linguistic disenfranchisement, minority resistance and language revitalisation: the contributions of ethnolinguistic online communities in Zimbabwe - Mpofu, Phillip; Salawu, Abiodun (Cogent, 2022)
Zimbabwe is a multicultural nation with multiple ethnolinguistic groups. Since 1980, when the country attained its independence from colonial rule, the government has struggled to fit all linguistic and cultural representations in the public domain. This resulted in disenfranchisement and disillusionment of linguistic minorities. However, the subject of ethnicity is sensitive and is to some extent associated with undertones of regionalism and division. Against this background, the disenfranchised linguistic minorities have taken advantage of the liberative potential of social media and are regrouping in the virtual space; in the process forming vibrant ethnolinguistic online communities. This study critically analyses the motivations and purpose of ethnolinguistic online communities on Facebook. This is a netnographic study of 10 purposively selected Facebook groups of linguistic minorities in Zimbabwe. The study is grounded in the concepts such as hegemony, hidden transcripts and alternative media. The findings of the study show that ethnolinguistic online communities provide the disenfranchised linguistic minorities with space and agency for protesting against marginalisation and language shift, in the process promoting the use of their languages. This study is a significant contribution to the growing body of scholarship on the nexus between language politics and social media in Zimbabwe.